"Dredging Method" - A Conservative Surgical Approach for the Treatment of Ameloblastoma of Jaw - Sadat, SMA; Ahmed, M (Journal of Bangladesh College of Physicians and Surgeons, 2011)
Ameloblastoma is an aggressive benign odontogenic tumor of jaws with different clinical features and histologic patterns. The resection of mandible in growing young patient is associated with number of complications such as loss of jaw bone support, deformity, dysfunction and psychological distress even after reconstruction. An alternative conservative surgical procedure "Dredging Method" is a procedure which can eradicate the tumor as well as restore the normal contour and function of jaw. The procedure was followed in twenty four cases of histologically confirmed mandibular ameloblastoma in Bangladeshi patients, with recurrence of three cases in an average of two years follow up. The recurrent cases could be handled easily due to early detection in regular follow up. DOI: http://dx.doi.org/10.3329/jbcps.v29i2.7951 (J Bangladesh Coll Phys Surg 2011; 29: 72-77)